Judgments about appropriate foods for infants: Associations with parents’ own food preferences - DeJesus, Jasmine M. (Frontiers in Nutrition, 2022)
When infants begin to eat solid foods (recommended at around 6 months of age), parents have a huge variety of choices in terms of what foods to offer. The present studies examine parents’ judgments about foods for infants. Participants included parents recruited from Prolific (n = 99), who were shown descriptions of foods offered to infants (including familiar and unfamiliar foods at 6-, 9-, and 12-months) and a set of control foods eaten by adults. Participants rated each food based on how appropriate they thought it was for an infant and how much they personally wanted to eat the food. Parents rated foods as more appropriate for infants if they were familiar (vs. unfamiliar) and offered to younger infants (6- vs. 12-month-olds, or infant foods vs. adult foods), but demonstrated the opposite pattern when considering whether they wanted to eat each food. Participants’ own food pickiness was related to their judgments about what they would eat, but not whether foods were appropriate for infants. Parents’ judgments of individual foods were inversely related: The more appropriate they rated each food for an infant, the less they were interested in eating that food. These findings are discussed in terms of potential barriers to engaging in social modeling (i.e., parents demonstrating eating and liking the foods they offer to their infants).